Büsserschnee in Vorderasien - Schweizer, Günther (ERDKUNDE, 1969)
Numerous recent observations of ’Büsserschnee’ deposits in the mountain ranges of the Near East serve as the base for a fresh investigation of the problems concerning the geographical distribution of true snow ’penitentes’ in this area. The ’Büsserschnee’ formations investigated by the author in the Kuh-e-Sabalan Massif (NW Iran) and the volcanic plug of the Demavend (Elburz, northern Iran) are described in some detail. The appearance of ’penitentes’ forms on the Kuh-e-Sabalan (4740 m) is of particular interest, since in the present state of research, it is the most northerly and westerly true ’Büsserschnee’ deposit in the entire Asian mountain system. Study of many glaciologic and alpinist reports on the Anatolian mountains allows the formation of ’Büsserschnee’ in that area to be firmly disregarded. There thus seems to be a clear boundary fence between Elburz, Kuh-e-Sabalan and the Zagros (?) on the one hand and the Caucasus, Ararat, Süphan Dagi and the Hakkâri Taurus on the other which separates the Near Eastern mountains with annual ’Büsserschnee’ in the east from those without periodic ’penitentes’ formation in the west.